Management and outcome of lower limb varicose veins: a hospital based follow up study - Reddy, G. V. Ramana; Abhilash, V.; Harshavardhan, Y.; Ravikiran, B. (International Surgery Journal, 2019)
Background: Disorders of veins which are chronic in nature and very common are the varicose veins. Surgery is required at any one stage of the disease. There have been considerable advances that took place in the diagnostics of the varicose veins, but the treatment outcomes may not be good in many cases. To study the management and outcome of lower limbs varicose veins. Methods: This was a hospital based follow up study. Patients who presented with varicose veins signs and symptoms were included. During the study period it was possible to include 40 patients who were willing to get included in the present study. Various presentations, complications and treatments were noted and finally followed up for minimum of 3 months. Results: Most commonly affected age group was 36-45 years. Males were four times more affected than females. Most commonly affected limb was left side in 48%. Long saphenous system was involved in 55%. The predominant symptom was dilated and tortuous veins (32%) followed by pain (25%). 65 incompetent perforators identified by clinical examination and 130 by Doppler with above ankle being the commonest incompetent perforator. With the mean follow up of six months, no serious complications were noted. It was found that the sensitivity of the clinical examination was 82% when doppler scan was taken as gold standard. On follow up no one developed deep vein thrombosis. Incompetence recurrence rate at SFJ was 8% and at SPJ was 18%. Conclusions: We conclude that surgery is the first line of management and if done accurately, complications are minimal.